2019
DOI: 10.1111/jfpe.13170
|View full text |Cite
|
Sign up to set email alerts
|

Using ultrasound for improving hydration and debittering of Andean lupin grains

Abstract: This article presents results about the potential use of ultrasound technology on the hydration and debittering process of Andean lupin grains (Lupinus albus Sweet). The hydration process was conducted conventionally and also assisted by ultrasound technology (ultrasonic water bath, 25 kHz, 41 W/L). Further than the hydration kinetics, the alkaloid content was evaluated. As results, the hydration kinetics of this grain showed a sigmoidal behavior, which was accelerated almost 40% using ultrasound. The lag phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 26 publications
1
19
1
Order By: Relevance
“…When water gradually penetrates into the grain, difference between the grain acoustic impedance and water acoustic impedance mails to zero. Therefore, it can be stated over time, energy losses decrease, and this makes influence of ultrasonication more prominent (Miano, Rojas, & Augusto, 2019a; Sun, 2014). Hence, it can be claimed, although soaking strategy and temperature solely increased water absorption rate of the grains in soaking process, higher temperature hindered contributory influence of the ultrasonication on water absorption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When water gradually penetrates into the grain, difference between the grain acoustic impedance and water acoustic impedance mails to zero. Therefore, it can be stated over time, energy losses decrease, and this makes influence of ultrasonication more prominent (Miano, Rojas, & Augusto, 2019a; Sun, 2014). Hence, it can be claimed, although soaking strategy and temperature solely increased water absorption rate of the grains in soaking process, higher temperature hindered contributory influence of the ultrasonication on water absorption.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, another strategy (ultrasonication) has been employed to proliferate water absorption of agricultural food products. Literature screening process confirmed that ultrasonication strategy was successfully utilized for soaking process of rice (Li et al, 2019; Wambura, Yang, & Wang, 2008), chickpea (Yildirim, Bayram, & Oner, 2012; Yildirim & Oner, 2015; Yildirim, Oner, & Bayram, 2010; Yildirim, Oner, & Bayram, 2011; Yildirim, Oner, & Bayram, 2013), bean (Ghafoor, Misra, Mahadevan, & Tiwari, 2014; Lopez et al, 2017; Miano & Augusto, 2018a; Miano, Pereira, et al, 2016; Miano, Rojas, & Augusto, 2019a; Miano, Sabadoti, & Augusto, 2018; Miano, Sabadoti, & Augusto, 2019; Ulloa et al, 2015), sorghum (Miano, Ibarz, et al, 2016; Patero & Augusto, 2015), melon (Miano, Ibarz, et al, 2016), sea cucumber (Zhang et al, 2016a, 2016b), carrot (Ricce, Rojas, Miano, Siche, & Augusto, 2016), corn (Miano, Ibarz, & Augusto, 2017), wheat (Guimaraes, Polachini, Augusto, & Telis‐Romero, 2020; Shafaei, Nourmohamadi‐Moghadami, & Kamgar, 2018; Shafaei, Nourmohamadi‐Moghadami, Rahmanian‐Koushkaki, & Kamgar, 2019), potato (Miano, Rojas, & Augusto, 2019b), barley (Borsato, Jorge, Mathias, & Jorge, 2019; Carvalho, Polachini, Darros‐Barbosa, Bon, & Telis‐Romero, 2018; Shafaei, Nourmohamadi‐Moghadami, & Kamgar, 2019), pumpkin (Rojas, Silveira, & Augusto, 2020), sesame (Shafaei, Nourmohamadi‐Moghadami, et al, 2021), and paddy (Kalita, Jain, Srivastava, & Goud, 2021). In these works, modeling of ultrasonication‐assisted soaking process of the products was commonly fulfilled with respect to soaking time using above‐mentioned nonlinear models for certain soaking temperatures and, constants and coefficients of the models varied with variations in soaking temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, another scheme (ultrasonication) has been employed to proliferate water absorption of agricultural food products. Literature screening process confirmed that ultrasonication scheme was successfully utilized for soaking process of rice (Li et al, 2019;Wambura et al, 2008), chickpea (Ranjbari et al, 2013;Yildirim et al, 2010Yildirim et al, , 2011Yildirim et al, , 2012Yildirim et al, , 2013Yildirim & Oner, 2015), bean (Ghafoor et al, 2014;Lopez et al, 2017;Miano & Augusto, 2018a;Miano et al, 2016bMiano et al, , 2019aMiano et al, , 2018Miano et al, , 2019cUlloa et al, 2015), sorghum (Miano et al, 2016a;Patero & Augusto, 2015), melon (Miano et al, 2016a), sea cucumber (Zhang et al, 2016a(Zhang et al, , 2016b, carrot (Ricce et al, 2016), corn (Miano et al, 2017), wheat (Guimaraes et al, 2020;Shafaei et al, 2018aShafaei et al, , 2019c, potato (Miano et al, 2019b), barley (Borsato et al, 2019;Carvalho et al, 2018;Shafaei et al, 2019a), pumpkin (Rojas et al, 2020), paddy (Kalita et al, 2021), and soybean (Shafaei et al, 2021a). In these works, modeling hydration kinetics of the food products was commonly fulfilled with respect to soaking time using above-mentioned nonlinear models for certain soaking temperatures, constants, and coefficients of the models varied with variations in soaking temperature.…”
Section: Introductionmentioning
confidence: 96%
“…In order to improve mass transfer processes, such as grain hydration, high-power ultrasound must be used. In fact, this technology has demonstrated a great acceleration of hydration process of grains such as chickpeas (Yildirim,Öner, & Bayram, 2010), navy beans (Ghafoor, Misra, Mahadevan, & Tiwari, 2014), sorghum kernels (Patero & Augusto, 2015), corn kernels (Miano, Ibarz, & Augusto, 2017), mung beans (Miano, Pereira, Castanha, Júnior, & Augusto, 2016), white kidney beans (Miano, Sabadoti, & Augusto, 2018), carioca beans (Miano & Augusto, 2018b), and Andean lupin (Miano, Rojas, & Augusto, 2019).…”
Section: Introductionmentioning
confidence: 99%